Stealth poly(lactic-co-glycolic acid) - diiodinated boron dipyrromethene nanoparticles to improve tumour selectivity in photodynamic cancer therapy / Voon Siew Hui - Voon, Siew Hui (2016)
Poor solubility and a lack of tumour selectivity are among the main issues limiting the clinical use of photosensitisers. Thus, various nanostructures have been reported as delivery agents for photosensitisers in an attempt to overcome these obstacles. However, these delivery agents suffer from premature clearance by the reticuloendothelial system (RES) and non-specific interactions with normal cells due to their hydrophobic surface. This study attempted to circumvent these problems via the application of a low molecular weight chitosan (25 kDa) “stealth” coating onto a nanoparticle-photosensitiser construct, using the poly(lactic-co-glycolic acid)-diiodinated boron dipyrromethene (PLGA-I2BODIPY) nanoparticle as a model. The chitosan coating altered the PLGA-I2BODIPY nanoparticle surface to become more hydrophilic and neutral charged without changing their size (average diameter of 147 nm) and morphology. In comparison with the uncoated control, the coated nanoparticles reduced burst release of I2BODIPY, increased cellular uptake predominantly at lysosomes and enhanced photocytotoxicity in 4T1 murine and MDA-MB-231 human breast cancer cells. PLGA-Chitosan-I2BODIPY nanoparticles also reduced serum protein adsorption and uptake by macrophages compared to the uncoated control. In 4T1 tumour bearing mice, the PLGA-Chitosan-I2BODIPY nanoparticles demonstrated better tumour selectivity and significantly reduced accumulation in tissues involved in RES such as lymph node, spleen and liver (by 10.2-, 2.1- and 1.3-fold, respectively), as well as non-tumour organs such as skin and eyes (by 22.7- and 4-fold, respectively) as compared to non-coated control. The PLGA-Chitosan-I2BODIPY and PLGA-I2BODIPY nanoparticles also showed increased therapeutic efficacy compared to free I2BODIPY. In conclusion, low molecular weight chitosan (25 kDa) is a promising “stealth coating” to evade premature RES clearance and improved tumour selectivity of PLGA nanoparticles.